Razvoj in izvedba proizvodnega informacijskega sistema s poudarkom na genealogiji - Rojec, Primož (Ventil (Ljubljana), 2007)
The Process Control Technology network (enterprises & institutions) has been involved in several projects approved and subsidised by the European Regional Development Fund. One of the subprojects is focused on process control and tracing in the electronics industry. A demo system has been implemented by Iskraemeco, d.d. in Kranj, Slovenia.
Keywords: elektronska industrija; genealogija; genealogy; informacijski sistemi; sledljivost